Academic identity and “education for sustainable development”: a grounded theory - Shephard, Kerry (Frontiers in Education, 2023)
The research described in this article set out to explore the nature of higher education institutions' commitment to teaching for social, environmental and economic justice in the context of the SDGs and to develop a theory of this phenomenon to support further research. The research used grounded theory methodology and took place over a two-month period in 2023. Cases were collected in four universities in New Zealand, India and Sweden and included interviews with individuals, participation in group activities including a higher education policy meeting, seminars and workshops, unplanned informal conversations, institutional policy documents and media analyses in the public domain. Cases were converted to concepts using a constant comparative approach and selective coding reduced 46 concepts to three broad and overlapping interpretations of the data collected, focusing on academic identity, the affective (values-based) character of learning for social, environmental and economic justice, and the imagined, or judged, rather than measured, portrayal of the outcomes or consequences of the efforts of this cultural group in teaching contexts. The grounded theory that derives from these three broad interpretations suggests that reluctance to measure, monitor, assess, evaluate, or research some teaching outcomes is inherent to academic identity as a form of identity protection, and that this protection is essential to preserve the established and preferred identity of academics.